2013
DOI: 10.1210/jc.2013-1977
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Periimplantation Uterine Natural Killer Cell Density in Human Endometrium Is Associated With Impaired Corticosteroid Signaling in Decidualizing Stromal Cells

Abstract: Background:Decidualizing human endometrial stromal cells (HESCs) profoundly up-regulate 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1), the enzyme that converts inert cortisone to active cortisol. We postulated that the induction of a cortisol gradient upon decidualization of the periimplantation endometrium may impact on the uterine natural killer (uNK) cell population and on local expression of corticosteroid-dependent target genes.Methods:Midluteal endometrial biopsies (n = 55) were processed for uNK cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…More recently, commercial tests for quantifying numbers of eNK cells in the luteal phase have been introduced, and steroid therapy is prescribed to those women with "high" levels (97,103,104). How numbers of mucosal NK cells might relate to their functions is not clear, particularly as there is a day-to-day increase during the luteal phase due to uNK cell proliferation.…”
Section: Nk Cells and Fertility Clinicsmentioning
confidence: 99%
“…More recently, commercial tests for quantifying numbers of eNK cells in the luteal phase have been introduced, and steroid therapy is prescribed to those women with "high" levels (97,103,104). How numbers of mucosal NK cells might relate to their functions is not clear, particularly as there is a day-to-day increase during the luteal phase due to uNK cell proliferation.…”
Section: Nk Cells and Fertility Clinicsmentioning
confidence: 99%
“…Approximately 15% of clinical pregnancies result in miscarriage 1 , most often during the first 37 trimester. Fetal chromosomal abnormalities account for 50-60% of sporadic miscarriages 2 , 38 although the incidence is lower in recurrent pregnancy loss (RPL) 3,4 , defined as two or more 39 losses 5,6 . Further, with each additional miscarriage, the frequency of euploid loss increases 40 whereas the likelihood of a successful pregnancy decreases 7 , indicating that uterine factors 41 drive higher-order miscarriages.…”
Section: Introduction 36mentioning
confidence: 99%
“…That 57% of women with three or more consecutive miscarriages involved in the study did not have an elevated uNK cell count demonstrates the complex nature of assessing the role of uNK cells in patients with RM. 34 Kuroda et al 16 demonstrated a difference in glucocorticoid signalling in patients with RM, and a higher proportion of uNK cells close to the luminal epithelium. uNK cells are normally found in surrounding perivascular cells and glands in the endometrial stroma.…”
Section: Recurrent Miscarriagementioning
confidence: 99%
“…Instead, the actions of progesterone on uNK cells are mediated via the glucocorticoid receptor (GR) . Progesterone enhances the expression and activity of 11BHSD type 1 in decidualising human endometrial stromal cells, thus increasing the conversion of cortisone to cortisol . Cortisol has a direct effect on the preparation of epithelial endometrial cells for implantation .…”
Section: Origins Of Uterine Natural Killer Cellsmentioning
confidence: 99%